The Holy Spirit as “the Gift” in Charles Nyamiti's Trinitarian Theology: A Pentecostal-Lutheran Dialogical Perspective - Kaunda, Chammah J. (Transformation, 2025)
This article starts from the theology of the Tanzanian-born Charles Nyamiti (1931–2020), as one of the most creative in his generation of African theologians. Nyamiti proposed that ancestral veneration is a foundational human relationship which reflects divine realities. Thus, he proposed an understanding of the Trinity where the Father is the Ancestor, the Son is the Descendant, and the Holy Spirit is the mutual Oblation connecting the two. Because an ancestor does not exist as an ancestor without sacred ritual communication, the Holy Spirit becomes thus absolutely necessary for the Godhead. We maintain that Nyamiti's ancestral approach describes an African logic of gift-giving. Translating his theological contribution into gift-language preserves the theological insights while solving some of the logical problems with the ancestral imaginary, such as how the Father who never died is supposed to be the Ancestor. Through gift-language, Nyamiti's theological insights, which are based on African relational ontologies, become more readily applicable in World Christianity and have potential to transform ecumenism into a vibrant and inclusive embodied pneumatic action for abundant life. In other words, Nyamiti's theological heritage invites theologians to envision Christian faith beyond the confines of Hellenistic-based philosophy.